KONSEP PEMERINTAH KOTA BANDA ACEH DALAM MEWUJUDKAN KOTA MADANI - Muzakkir Zabir (Kalam: Jurnal Agama dan Sosial Humaniora, 2017)
Civil society in principle has the systemic, democratic society, ethics and morality, transparency, tolerance, potential, aspirational, motivated, participated, consistent comparison, able to coordinate, simple, synchronized, integral, recognize, emancipation and rights, but the most dominant is a democratic society. Civil society is a social society that will protect citizens from the excessive manifestation of state power. Civil society even becomes the main pillar of democratic political life. Because civil society not only protects citizens in dealing with the state, but also to formulate and articulate people's aspirations.